Diraḫt-i suḫan, bār-i dāniš - Taǧlīl, Ǧalīl,Raṯī Tihrānī, Ḥabīb,Yazdī Mihr, ʿUḏrā (Našr-i ʿIlmī, 2015)
Persian literature – History and criticism
Keywords: Aufsatzsammlung; Persisch; Sufismus; Literatur; Kritik